Using Android-Based Learning Media Using Smart Apps Creator (SAC) to Increase Motivation Students Learn Biology - Sugiyono, Sugiyono (UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of writing this Best Practice is to find out whether the use of Android-based learning media with the Smart Apps Creator (SAC) can increase the motivation to learn biology for SMA Negeri 3 Palembang students. This type of research is Classroom Action Research (CAR), which consists of two cycles. The research subjects were students of class X IPA SMA Negeri 3 Palembang in the 2022/2023 academic year, with a total of 21 students consisting of 13 girls and 8 boys. Data collection techniques in this study were observation, questionnaires, tests and documentation. The data analysis technique used is descriptive qualitative analysis. Learning Outcomes by using an android application which contains motion system material takes place actively, students are motivated to explore the material provided by the teacher through the application. They discussed in their respective groups with enthusiasm. This gives them a new experience on how to use Android for learning in a more interesting way. Based on the results of the implementation of learning using Android-based learning media with the Smart Apps Creator (SAC) application, results showed an increase in learning motivation of students in class X IPA SMA Negeri 3 Palembang. The results of students' responses to Android-based learning media on motion system material for class class X IPA SMA Negeri 3 Palembang. is Good, with a percentage of 76.44%.